Increased oral lichen planus in a chronic hepatitis patient associated with elevated transaminase levels before and after interferon/ribavirin therapy - Shin-Yu Lu; Liang-Ho Lin; Sheng-Nan Lu; Jing-Houng Wang; Chao-Hung Hung (Journal of Dental Sciences, 2009)
Oral lichen planus (OLP) is the most frequent oral lesion found in patients with hepatitis C virus (HCV) infection. The aims of this study were to investigate the prevalence of OLP among chronic hepatitis C patients, to clarify the role of HCV in the pathogenesis of OLP, and to assess its relationship to transaminase levels. Materials and methods: Two groups of subjects were studied; 277 hepatitis C patients were examined for OLP (Group 1) and 5273 outpatients seeking dental care within 1 year were used as a control (Group 2) to determine the prevalence of OLP in the general population. The dental and hepatic records were collected and analyzed. Results: The prevalences of OLP were 4.7% (n = 13) in Group 1 and 2.0% (n = 104) in Group 2 and significantly differed (P = 0.002). All 13 OLP cases occurred in hepatitis C patients who had experienced elevated alanine transaminase levels of > 80 IU/L within the 2 previous years, regardless of whether they were treated with interferon-ribavirin combination therapy or not. There was a strong association between elevated transaminase levels and the development of HCV-related OLP lesions (P = 0.014). Of the 13 OLP patients, two were in the group with a sustained virologic response (SVR) to HCV therapy, two were in the group without an SVR, and nine were in the non-therapy group. The incidence of OLP in hepatitis C patients did not significantly differ between those who showed an SVR to HCV therapy and those who did not respond or did not receive therapy (P = 0.560). Conclusion: We concluded that: (1) elevation of transaminase levels is associated with the detection of HCV-related OLP, and (2) HCV-related OLP can remain unchanged for years after an SVR to HCV therapy. The findings revealed that the role of HCV in OLP pathogenesis is due to host factors induced by HCV rather than a direct cytopathic effect of HCV.